Implementation of the ecosystem services approach in Swedish municipal planning. Issue 3 (4th May 2018) - Schubert, Per; Ekelund, Nils G. A.; Beery, Thomas H.; Wamsler, Christine; Jönsson, K. Ingemar; Roth, Andreas; Stålhammar, Sanna; Bramryd, Torleif; Johansson, Michael; Palo, Thomas
ABSTRACT: While ecosystem-based planning approaches are increasingly promoted through international and national policies, municipalities are still struggling with translating them into practice. Against this background, this paper aims to increase the knowledge of current advances and possible ways to support the implementation of the ecosystem services (ES) approach at the municipal level. More specifically, we analyze how ES have been integrated into comprehensive planning within the municipality of Malmö in Sweden over the last 60 years, a declared forerunner in local environmental governance. Based on a content analysis of comprehensive plans over the period 1956–2014 and interviews with municipal stakeholders, this paper demonstrates how planning has shifted over time toward a more holistic view of ES and their significance for human well-being and urban sustainability. Both explicit and implicit applications of the ES concept were found in the analyzed comprehensive plans and associated programs and projects. Our study shows how these applications reflect international, national, and local policy changes, and indicates how municipalities can gradually integrate the ES approach into comprehensive planning and facilitate the transition from implicit to more explicit knowledge use.